Parenting stress and Chinese preschoolers’ approaches to learning: a moderated mediation model of authoritative parenting and household residency - Zhao, Jinghui; Fan, Yizhen; Liu, Ziqin; Lin, Chaopai; Zhang, Limin (Frontiers in Psychology, 2023)
According to the family stress model, this study examined the relationship between parenting stress and preschoolers' approaches to learning (ATL) in China, as well as the mediating effect of authoritative parenting and the moderating effect of household residency (migrant and native). A survey of 5047 preschoolers' parents (2186 natives and 2861 migrants) supports the proposed moderated mediation model. The results showed that after controlling for gender and age, parenting stress affected preschoolers' development of ATL negatively. Authoritative parenting mediates the relationship between parenting stress and preschoolers' ATL. Further, household residency moderated the relationship between authoritative parenting and preschoolers' ATL. The findings of this study suggest that high levels of parenting stress are detrimental to the development of preschoolers' ATL. And parents with low parenting stress are more likely to adopt authoritative parenting, which in turn fosters preschoolers' ATL. In addition, native families' authoritative parenting style are more conducive to fostering preschoolers' ATL than migrant families. Finally, this study contributes to previous research by examining the mechanisms of parenting stress on preschoolers' ATL and provides support for the extension of the family stress model. Importantly, it also informs efforts to improve ATL among preschoolers in Chinese migrant and native families.